Review of Tumor Dormancy Therapy Using Traditional Oriental Herbal Medicine - Lee Jong-Ho; Koung Fan-Pei; Cho Chong-Kwan; Lee Yeon-Weol; Yoo Hwa-Seung (Korean Pharmacopuncture Institute, 2013)
Objective: Standard cancer therapy prolongs survival, but can be detrimental to the quality of life, compromise the immune system, and leave residual disease that can cause recurrence years or decades in the future. Tumor dormancy therapy is a novel therapeutic approach that may improve these shortcomings, promote quality of life, and prolong survival. The aim of this study was to analyze studies on dormancy therapy, especially studies using traditional Oriental herbal medicine, so as to evaluate the efficacy of dormancy therapy with traditional oriental herbal medicine. Methods: We conducted a systematic literature review using Scientific and Technical Information Integration Services (NDSL), PubMed, and RISS. We searched for clinical reports, papers, and books related to tumor metastasis, recurrence, immunotherapy, tumor dormancy, and traditional oriental herbal medicine with anticancer effects. Seventy-nine (79) experimental and clinical articles in both Korean and English were reviewed. This study was conducted from March 1, 2012 to May 31, 2012. Results: This approach, Tumor dormancy therapy, rather than seeking to remove the tumor, includes combination of low-dose chemotherapy, immunotherapy, immunosurveillance, and other methods to stabilize tumor growth and to enhance the host is immunity against disseminated tumor cells and thus to manage cancer as a chronic disease while maintaining quality of life. In particular, integrative use of Oriental herbal medicine has been shown to induce or maintain tumor dormancy, increase the effectiveness of conventional chemotherapy, improve quality of life, and prolong survival. Conclusion: Tumor dormancy therapy is a promising novel therapeutic approach that may be especially effective with Oriental herbal medicine. Further research is needed to determine its potential mechanisms and therapeutic applications.